A Collective Algorithmic ApproachFor Enhanced DNA Database Security - Arputharaj J, Vijay; Manicka Chezian, Dr.R. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The proposed method is a mixture of several security methods namely digital authentication tag along with the data mining in the DNA database. Data mining in the area of human genetics, an important goal is to understand the mapping relationship between the individual variation in human DNA sequences and variability in various algorithms for database security issues, for mutation susceptibility and parental identification differences. This paper primarily deals with the advancement of genetic algorithm with proper security features in DNA Databases and it enhances the special features in DNA database security. Several security methods include encryption algorithms, higher, not as much of multifaceted with trouble-free to apply in DNA Databases, used for protected database. The Reverse Encryption algorithm to protect data,Advance Cryptography algorithm to resist data, also Advanced Encryption Standard (AES) is most preferable for security in DNA databases.